A resource-based habitat view for conservation : butterflies in the British landscape - Dennis, Roger L. H.; Wiley eBooks (Chichester, UK ; Hoboken, NJ : Wiley-Blackwell, 2010)
"In A Resource-Based Habitat View for Conservation Roger Dennis introduces a novel approach to the understanding of habitats based on resources and conditions required by organisms and their access to them, a quantum shift from simplistic and ineffectual notions of habitats as vegetation units or biotopes. In drawing attention to what organisms actually use and need in landscapes, it focuses on resource composition, structure and connectedness, all of which describe habitat quality and underpin landscape heterogeneity. This contrasts with the current bipolar view of landscapes made up of habitat patches and empty matrix but illustrates how such a metapopulation approach of isolated patchworks can grow by adopting the new habitat viewpoint." "The book explores principles underlying this new definition of habitat, and the impact of habitat components on populations, species' distributions, geographical ranges and range changes, with a view to conserving resources in landscapes for whole communities. It does this using the example of butterflies - the most alluring of insects, flagship organisms and key indicators of environmental health - in the British Isles, where they have been studied most intensively." "The book forms essential reading for students, researchers and practitioners in ecology and conservation, particularly those concerned with managing sites and landscapes for wildlife."--Jacket.
Front Matter -- What is a Habitat? An Awkward Question -- A Simple Model for Butterfly Habitats -- Basic Principles for Butterfly Habitats -- Exploiting Individual Resources -- Butterfly Habitats: Searching for Order -- The Habitat Context for Butterfly Populations -- Landscape Influences on Butterfly Habitats -- Habitat Issues in Butterfly Geographical Ranges -- Habitats in Butterfly Conservation -- Appendix 1: Biodiversity Action Plan (BAP) Status, Legal Protection and Taxonomic Relationships for British Butterflies -- Appendix 2: Larval Hostplants for British Butterflies -- Appendix 3: Nectar Sources of British Butterflies -- Appendix 4: Statistics on Larval Host Use and Adult Feeding in British Butterflies -- Appendix 5: Utility Resources and Life History Data on British Butterflies -- Appendix 6: Adult and Larval Behaviour in British Butterflies -- Appendix 7: Biotopes for British Butterflies -- References -- Index.
Includes bibliographical references and index.
Electronic reproduction.
John Wiley and Sons
Keywords: Butterflies -- Habitat -- Conservation -- Great Britain; Butterflies -- Ecology -- Great Britain; Butterflies -- Monitoring -- Great Britain; Wildlife conservation -- Great Britain; Electronic books